2017
DOI: 10.1111/jdv.14599
|View full text |Cite
|
Sign up to set email alerts
|

Low and high body mass index in hidradenitis suppurativa patients—different subtypes?

Abstract: Patients with a low and high BMI could represent two clinically different subtypes. We suggest a non-linear relationship between BMI and impact of HS. As patients go from a low BMI patient to a high BMI patient (or from high to low), eruption patterns and risk factors may change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 24 publications
1
39
1
2
Order By: Relevance
“…HS consists of many phenotypic presentations including the following: classic vs atypical, inflammatory vs occlusive follicular, early vs late onset and indolent vs fulminant . Further studies of the genetic background of the disease, clinical presentations, pathophysiology and associated co‐morbidities guide the understanding of the natural history of the disease.…”
Section: Scientific Session 4: Clinical Presentations Of Hidradenitismentioning
confidence: 99%
“…HS consists of many phenotypic presentations including the following: classic vs atypical, inflammatory vs occlusive follicular, early vs late onset and indolent vs fulminant . Further studies of the genetic background of the disease, clinical presentations, pathophysiology and associated co‐morbidities guide the understanding of the natural history of the disease.…”
Section: Scientific Session 4: Clinical Presentations Of Hidradenitismentioning
confidence: 99%
“…41 A cross sectional study, compared 205 HS patients with a high (above 35) body mass index (BMI) with 246 HS patients with a low BMI (below 25). 42 Those with a high BMI significantly suffered more severe disease (Hurley, PGA, number of areas affected and patient reported severity) and patients with low BMI significantly reported greater severity when they increased their BMI. 42 The authors concluded patients with a low and high BMI could represent two clinically different subtypes of HS suggesting a non-linear relationship between BMI and impact of HS.…”
Section: -Obesity and Other Endocrine Abnormalitiesmentioning
confidence: 99%
“…42 The authors concluded patients with a low and high BMI could represent two clinically different subtypes of HS suggesting a non-linear relationship between BMI and impact of HS. 42 The role of androgens and sexual hormones remains controversial, 34 but many facts support a possible relation: -the typical onset in a narrow age spectrum after puberty; -rare postmenopausal onset 34 ; -usual improvement during pregnancy and post-partum flare-up 34 ; -reports of association with irregular menses, hirsutism and higher concentration of total testosterone, 43 although not constant 28,44 ; -reports of significant remission after antiandrogen therapy, although most of HS patients have normal androgen profiles 45,46 ; -HS in children under 12 is more likely associated with hormonal imbalance, namely adrenal hyperplasia, premature adrenarche, obesity, and metabolic syndrome. 47 In fact, a diagnosis of HS in children may be a marker of precocious puberty.…”
Section: -Obesity and Other Endocrine Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…On this subject matter, note that in HS mTOR gene expression statistically correlates with the severity of the disease and, like in acne vulgaris [23], with the body mass index (BMI) [13]. Recently, it has been suggested that patients with a low and high BMI could represent 2 clinically different subtypes, since eruption patterns and risk factors may change depending on the BMI value [24]. Consequently, isotretinoin might exert major anti-inflammatory effects in patients with a higher BMI.…”
mentioning
confidence: 99%